Policy Formulation Process on Indonesian Capital City Development East Kalimantan - Anggara Setya Saputra; Supardi Hamid; I Gusti Kade Budhi Harryarsana (Department of Public Administration, 2023)
The issue of relocating the capital city has become the main target in accelerating the movement and development of the government to meet the progress of implementing the planned program in all fields the community. This makes the process of moving the capital city into one of the strategic efforts taken by the global route systematically by the government in maintaining national integrity and government governance of the life of the nation and state. In east Kalimantan the research was conducted using the literature review approach, which has the aim of trying to compare and quote based on the results of the same research regarding the study of policy formulation. The literature review method generally contains a review, summary of author’s thoughts on several library sources such as articles, books, information the internet and others. The results of the study show that in the process of formulating the Nusantara IKN development policy in East Kalimantan it has become a major policy that can have a direct effect on the community in all fields that are matters of public interest. In the process of formulating the IKN Nusantara development policy in East Kalimantan, systematic and detailed aspects and indicators are needed in preparing everything that can contribute directly and encourage the development of the Nusantara IKN such as aspect and indicators such as the Nusantara IKN development plan, the development process alternative policy options for the development of the Nusantara IKN and testing alternative policy option through the results of deliberation and consultation in determining alternative solutions and the parties involved in the process of formulating detailed spatial plans for strategic areas of the national capital city. It is also necessary to pay attention to the ability of the involvement of each actor in the development process because it is very influential on the progress of the development of the Nusantara IKN in accordance with the expectations set by the government for the transfer of the Nusantara IKN.